Developing Writing Through Blogs and Peer Feedback - Gómez Delgado, Oscar Mauricio; McDougald, Jermaine S. (Íkala, Revista de Lenguaje y Cultura, 2014)
Results are presented from a study conducted online with a population of students of an English teacher education program. The study inquired into the role that peer feedback played in the development or maintenance of coherence in non-fictional narrative blog writing. Participant students produced narrative blog entries and peer feedback, which were double-assessed to establish the possible relationship between feedback and coherence. Learner's logs were also kept to obtain second-order data. Findings suggest that peer-feedback and blogging can act as boosting factors to enhance or maintain levels of coherence in text, through the shaping of students' cognition and affection. The potential is revealed of student-centered strategies to enhance learning and foster autonomy through a higher degree of student's control over learning. In addition, it is proposed that new language assessment paradigms be applied in the classroom, acknowledging students as a valid and reliable source of assessment information.